Literature Study on the Utilization of Electromagnetic Waves in the Health Sector - Sinaga, Erdina Sari; Handayani, Fitri; Hutagalung, Nazma Yanti; Rifandha, Surya Azi; Lubis, Rajo Hasim (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
The rapid development of natural sciences, especially in developing the concept of physics in the health sector. Its utilization can facilitate the healing of diseases, such as using electromagnetic waves in healing diseases. This study aims to determine the benefits generated from electromagnetic waves that can help and facilitate the handling of diseases in the health sector by using a literature study method that utilizes information retrieval from several journals and trusted sources. Electromagnetic waves can be used in X-rays. Areas of the body that need to be examined through emitted X-rays. Ultrasonogram (USG) is a medical equipment used in tomography to see the fetus's condition and others where all of that is the use of Physics in the Utilization of Electromagnetic Waves which helps the health sector.